Find ((d^2)/dx^2)*(2e^(-3x))?

any help is greatly appreciated!

2 Answers

  • MyRank
    Lv 6
    4 weeks ago

    d²/dx² (2e⁻³x) = ?

    d/dx (2e⁻³x) = 2 x (-3) e⁻³x= -6e⁻³xd²/dx² (2e⁻³x) = d/dx (-6e⁻³x)= 6 x (-3) x e⁻³x= +18e⁻³x.

  • Roger
    Lv 7
    4 weeks ago


    The first derivative of e^(nx)

    (d/dx)(e^(nx)) = ne^(nx)

    and the derivative of   ne^(nx) is

    (d/dx)(ne^(nx))=  n²e^(nx)

    which is the second derivative (d²/dx²) e^(nx)


    so for 2e^(-3x)

    the first derivative is -6e^(-3x)

    and the second derivative is


Still have questions? Get answers by asking now.